Functional gastrointestinal disorders are associated with the joint hypermobility syndrome in secondary care: a case–control study. Issue 4 (April 2015) - Fikree, A.; Aktar, R.; Grahame, R.; Hakim, A. J.; Morris, J. K.; Knowles, C. H.; Aziz, Q.
Abstract: Background: The overlap of unexplained gastrointestinal (GI) and somatic symptoms is well established in patients with functional gastrointestinal disorders (FGID). Joint hypermobility syndrome (JHS) is a non‐inflammatory connective tissue disorder associated with GI and somatic symptoms. We aimed to determine whether there is an association between diagnosis of JHS and FGID and the impact of this association on comorbidities and quality of life (QOL). Methods: Prospective case–control study in secondary care GI clinics over 2 years. JHS was assessed by the first author prior to consultation in 641 consecutive new patients. Diagnosis of FGID (cases, n  = 336) or organic disorders (controls, n  = 305) was established blind to JHS status. JHS prevalence was compared in cases (FGID patients) and controls (organic disorders patients). Extra‐intestinal comorbidity and QOL were compared in FGID patients with and without JHS. Key Results: JHS prevalence was higher in FGID compared to organic GI disorders (39.0% vs 27.5%, ORadj: 1.51, CI: 1.07–2.12, p  = 0.02), and particularly associated with functional gastroduodenal disorders (44.1%, ORadj: 2.08, CI: 1.25–3.46, p  = 0.005), specifically postprandial distress syndrome (51%, ORadj: 1.99, CI: 1.06–3.76, p  = 0.03). FGID patients with JHS had increased chronic pain (23.2% vs 11.9%, p  = 0.01), fibromyalgia (10.5% vs 3.1%, p  = 0.01), somatization scores (13 vs 10, p  < 0.001), urinary autonomic scores (30.5 vs 20.7, p  = 0.03), and worse pain‐related QOL scores (45.0 vs 63.5, p  = 0.004). Conclusions & Inferences: JHS is significantly associated with FGID, and this subgroup of patients have increased comorbidity and decreased QOL. Further research is required to understand the pathophysiological basis of this association. Abstract : The prevalence of joint hypermobility syndrome (JHS) in patients with Functional gastrointestinal disorders (FGID) has not been studied prospectively. In patients presenting to secondary care GI clinics, JHS is more common in patients with FGID in comparison to those with organic GI disorders; JHS is most‐significantly associated with functional gastroduodenal disorders, specifically postprandial distress syndrome. Patients with overlapping JHS and FGID have a phenotype characterized by increased chronic pain, somatic sensitivity, autonomic symptoms, psychological manifestations of anxiety, and reduced quality of life.